A generalização obtida pelo modelo ABAB-Retirada e provas múltiplas em diferentes graus de severidade do desvio fonológico - Barberena, Luciana da Silva (2005)
This study was carried out to analyze the structural generalization obtained by the ABAB withdrawal and multiple tests among children with different degrees of phonological deviations. The diagnosis was determined by the speech-language and hearing evaluation as well as phonological analysis and complementary tests. The subjects of this research were 8 children, 4 of them were female and 4 were male, with the age mean 5,5. For the subjects selection, the criterion was that they should had not presented significant disorders in the evaluations, except the phonological one. The phonological evaluation has revealed disorders at the phonological level and a shortened phonetic inventory, with a significant impairment in the speech intelligibilty. The data analysis was based on the Child s Phonological Evaluation (Yavas, Hernandorena and Lamprecht, 1991) and such evaluation was carried out at the beginning and at end of the treatment. After the contrastive analysis, the subjects were distributed into four groups as follows: the severe group, moderatesevere group, medium-moderate group and, the moderate group, according to the degree of the phonological deviations based on the Percentage of Correct Consonants (PCC) (Shriberg e Kwiatkowski, 1982). Each of the four groups was composed of two individuals. The phonological treatment applied was the ABAB withdrawal design and multiple tests (Tyler e Figurski, 1994), considering the Implicational Model of Features Complexity (Mota, 1996). After the treatment, the description and analysis of the phonological system and the phonetic inventory as well as the occurrence of the impairments of the distinctive features before and after the treatment had been carried out. The analysis of the development of the therapy by the generalization was observed through the comparison between the two analyses: the contrastive and the distinctive ones by the time of evaluation and reevaluation (generalization tests and targeted-basic tests). The following types of generalization were analyzed: to non-used items during treatment (other words), to other position in the word, inside a sound class, to other sound class, to other syllable structuring and, based on the implicational relationships. All types of structural generalization analyzed were found in the four groups. Concerning the phonetic inventory, the phonological system and the occurrence of distinctive features before and after the treatment, it was found that all degrees of phonological deviation have demonstrated some improvement, however, the severe degrees were the ones which have presented the highest improvement among the different degrees.